BCG and vole bacillus vaccines in the prevention of tuberculosis in adolescence and early adult life. Issue 6082 (30th July 1977) - Hart, P D; Sutherland, I
Abstract : The Medical Research Council's trial of BCG and vole bacillus vaccines in the prevention of tuberculosis in Great Britain has ended after 20 years' follow-up of the 54 239 participants, who were aged 14 to 15 years when the entered the trial in 1950-2. Participants who were tuberculin positive on entry were left unvaccinated; those who were tuberculin negative were allocated at random to an unvaccinated or to a vaccinated group. The protective efficacy of each of the two vaccines, among those initially tuberculin negative, was 84% during the first five years, and gradually decreased, averaging 77% for each vaccine over the whole period. The incidence of tuberculosis decreased substantially in all groups during the trial, however, and of the total of 610 cases of tuberculosis only 27 developed between 15 and 20 years. Thus we cannot make a reliable assessment of efficacy during this final period. The prevalence and incidence of tuberculosis in Great Britain have decreased radically since this trial began. The expected benefit from large-scale BCG-vaccination of children is now far less, and may decrease further if the incidence of tuberculosis continues to decline.